Kepatuhan terhadap Regimen Terapeutik pada Penderita Hipertensi di Kalangan Awak Kapal Motor - Akhmad Khunaeni; Ani Haryani; Dewi Rahmawati; Darwis Manto Juli Manihuruk (Universitas Faletehan, 2026)
Hypertension is a chronic disease that requires long-term adherence to medication and lifestyle modifications. Maritime working conditions, such as rotating work patterns, limited space, and limited access to healthcare, can be barriers to compliance. This study aimed to describe compliance with the therapeutic regimens of hypertension among the crew of motorboats. A descriptive quantitative study with a cross-sectional approach was conducted in April–June 2025 to 129 respondents who were purposively selected from 156 crew members with hypertension. Data were collected using an online questionnaire based on the Health Belief Model and patient compliance theory, covering five domains: hypertension management, medication adherence, diet, physical activity, and stress management. Of the 30 items, 26 were declared valid with very good reliability (α=0.938). The analysis was carried out univariately. The results showed that most of the respondents were ≥50 years old (45.7%) and had a working period of >20 years (54.3%). As many as 61.2% had good compliance. The highest proportion was found in hypertension management (83.7%), followed by stress management (75.2%), diet (68.2%), physical activity (64.3%), and medication adherence (54.3%). The majority of the crew showed relatively good adherence, but medication adherence was still lowest. It is necessary to strengthen education, monitor drug compliance, and ensure the availability of drugs during the voyage.